The role of education in achieving sustainable social development (Journal of Misan Researches, 2024)
This research aims to highlight the role of education in achieving sustainable social development; If social development is seen as the right to a healthy and empowering life, it is clear that education is a powerful enabling factor and an important aspect of social development, and whether we understand education as knowledge and skills that young people acquire in schools or as an infrastructure that can be used to implement interventions, Education is pivotal in ensuring that people are able to live healthy lives and improve the lives of their children. Learning can also have powerful transformative effects in advancing gender equality in societies and strengthening mandate, voice and participation for vulnerable populations, but how will this be achieved?         This research explores the role of accountability in education at all levels, recognizing that the various actors operating within and across countries are responsible for the future of the SDGs; the challenges facing societies are enormous and urgent, and the more general role that education and lifelong learning can and should play is not always fully appreciated. Therefore, the need to integrate equitable and good quality education into the agenda of sustainable development goals should be the main hope for education and development groups. How will the world monitor progress in many of the ambitious goals of sustainable social development? A framework has been developed that monitors education as an effective pivotal indicator. to enable.